The Relation Between Preschoolers’ Cognitive Distraction Strategies and Problem Behaviors: Social Skills as a Mediator and Delay of Gratification as a Moderator - Cansu Tutkun (Journal of Educational Issues, 2024)
This study aims to investigate the relation between preschoolers’ social skills as a mediator and delay of gratification as a moderator, and their cognitive distraction strategies and problem behaviors. The participants of this study were 100 randomly selected preschoolers aged 3 to 5 years, who were attending a private preschool in Ankara, the capital of Turkey. Data was obtained through Marshmallow Test to evaluate cognitive distraction strategies with regard to delay of gratification, and the Social Skills Improvement System Rating Scales (SSIR-RS) to assess the preschoolers’ social skills and problem behaviors. The obtained data was analyzed with correlation analysis and mediator variable analysis. The findings revealed that preschoolers’ cognitive distraction strategies, social skills, and problem behaviors are significantly correlated. Besides, as problem behaviors of the preschoolers increased, their use of social skills and cognitive distraction strategies decreased. Furthermore, it was determined that cognitive distraction strategies were a significant predictor of problem behaviors. Finally, it was concluded that social skills had a mediating role in the relationship between preschoolers’ cognitive distraction strategies and their problem behaviors. These findings highlight possible interventions to boost children’s development by enhancing their social skills and cognitive distraction strategies, as well as reducing problem behaviors.